The 2015 Borneo fires: What have we learned from the 1997 and 2006 El Niños? - Chu-Chun Chen; Hsiao-Wen Lin; Jin-Yi Yu; Min-Hui Lo (Environmental Research Letters, 2016)
Fire activity in Indonesia is strongly linked with El Niño events, whose sea surface temperature (SST) patterns can weaken the Walker circulation to induce drought conditions in the region. Here we show via case analyses and idealized climate model simulations that it is the central location of the SST anomalies associated with El Niño, rather than its strength, that is mostly linked with the fire occurrence. During our study period of 1997–2015, Eastern Pacific (EP) El Niño events produced the largest fire events in southern Borneo (i.e., in 1997, 2006, and 2015), while Central Pacific (CP) El Niño events consistently produced minor fire events. The EP El Niño is found to be more capable than the CP El Niño of weakening the Walker circulation that acts to prolong Borneo’s drought condition from September to October. The extended dry conditions in October potentially increase the occurrence of fires during EP El Niño years. The 2015 fire event owes its occurrence to the location of the 2015 El Niño but not necessarily its ‘Godzilla’ strength in affecting the fire episodes over southern Borneo. Projecting the location of El Niño events might be more important than projecting their strength for fire management in southern Borneo.